The Effect of Green Banking and Green Investment on Firm Value with Eco-Efficiency as Moderation - Murwaningsari, Etty; Rachmawati, Sistya (IJOSMAS, 2023)
The purpose of this research is to analyze the effect of (1) green banking and green investment on firm value. (2) Eco-efficiency moderates green banking and green investment on firm value. This research method was carried out by taking secondary data, namely banks listed on the Indonesian stock exchange (IDX-IC), the number of research samples was 47 banks, according to purposive sampling criteria during the 2016-2021 period (6 years) so the number of samples was 107 observations, using panel data regression. The results of this study (1) Green banking has a positive effect on firm value. (2) Green investment has a positive effect on firm value. (3) Eco-Efficiency can strengthen the effect of green banking on firm value. (4) Eco-Efficiency cannot strengthen the effect of green investment on firm value